2022
DOI: 10.1093/infdis/jiac092
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Activities Against the Omicron Variant After a Heterologous Booster in Healthy Adults Receiving Two Doses of CoronaVac Vaccination

Abstract: Background The use of an inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine (CoronaVac) against SARS-CoV-2 is implemented worldwide. However, waning immunity and breakthrough infections have been observed. Therefore, we hypothesized that the heterologous booster might improve the protection against the delta and omicron variants. Methods A total of 224 individuals who completed the two-dose Coron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 48 publications
11
59
0
Order By: Relevance
“…However, the NAb titers against omicron were retained upon booster vaccination even though the current vaccines composition was based on the ancestral strain. Consistent results were observed after receiving mRNA vaccine following either homologous inactivated, adenoviral-vectored, or mRNA-based vaccines prime [14,21,22,30]. Although the low number of omicron-neutralizing memory B-cells produced after two-doses of mRNA vaccination has previously been reported, their coverages were improved through affinity maturation over time and might be sufficient to expand the coverage of neutralization against SARS-CoV-2 variants after receiving a booster dose [31].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, the NAb titers against omicron were retained upon booster vaccination even though the current vaccines composition was based on the ancestral strain. Consistent results were observed after receiving mRNA vaccine following either homologous inactivated, adenoviral-vectored, or mRNA-based vaccines prime [14,21,22,30]. Although the low number of omicron-neutralizing memory B-cells produced after two-doses of mRNA vaccination has previously been reported, their coverages were improved through affinity maturation over time and might be sufficient to expand the coverage of neutralization against SARS-CoV-2 variants after receiving a booster dose [31].…”
Section: Discussionsupporting
confidence: 74%
“…It was found that individuals who received the heterologous CoronaVac/AZD1222 vaccination exhibited a 5.9-fold reduction in binding antibody and less detectable NAbs to omicron variants after 4 to 5 months post-second dose, indicating waning of vaccine-induced immunity [10]. It has been well established that booster vaccinations could overcome the waning immunity [14,21,22,28]. Rapid elevation in binding antibodies after boosting with mRNA and adenoviral-vectored vaccines were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 Booster vaccines are needed to increase neutralizing antibodies in fully vaccinated individuals. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 However, different booster vaccines significantly increased neutralizing antibodies (NAbs) in patients with two doses of inactivated vaccines, including the omicron variant. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%